Keanekaragaman Amfibi Ordo Anura di Blok Perlindungan dan Blok Pemanfaatan Hutan Pendidikan Konservasi Terpadu, Taman Hutan Raya Wan Abdul Rachman (The Diversity of Amphibian from Order Anura in the Protected and Utilization Blocks of Integrated Educational Conservation Forest, Wan Abdul Rachman Great Forest Park) - Siahaan, Kornelius; Dewi, Bainah Sari; Darmawan, Arief (Jurnal Sylva Lestari, 2019)
Amphibians are part of biodiversity that spread in various places in the world. Amphibians have an important role in maintaining the balance of the ecosystem as part of the food chain system. However, lack of public understanding caused the potential of Anura amphibians to have not been explored optimally hence research on Anura amphibians in the Wan Abdul Rachman Great Forest Park (Tahura WAR) is very important to support Anura's conservation efforts. This study aims to understand and identify the diversity of Anura order amphibians in the Protection and Utilization Blocks of the Tahura WAR on forest and river habitat types. Data was collected by using Line Transect and Visual Encounter Survey method. Data collection using Line Transect was conducted by making a narrow transverse path at the observation site, while the Visual Encounter Survey was conducted by making a wildlife observation path with 3 replications. Analysis of the data used included amphibian diversity, community similarity index, and species evenness. The results found 25 individuals of Anura amphibians in the Protection Block and 40 individuals in the Utilization Block of Tahura WAR. Overall, 65 individuals were found consisting of 3 species of amphibians from 2 families i. e., 2 species of the Ranidae family and 1 species of the Bufonidae family. The results showed that the species diversity index, species richness index, and community similarity index in the Protection and Utilization Blocks of Tahura WAR were categorized as low. Reforestation needs to be done so that the Anura habitat is maintained. Keywords: amphibian, biodiversity, order Anura, Tahura WAR